Coating modified precursor material and preparation method thereof, coating modified positive electrode material and preparation method thereof, and lithium ion battery
Through the technology of covering modified positive electrode materials, the double-layer coating of KNbO3 and MoS2 composite materials and Li7SbO6 is solved, and the problem of unstable electrochemical performance of ternary positive electrode materials in lithium-ion batteries is significantly improved, and the battery capacity and circulation are significantly improved. Lifetime improves charge separation efficiency and electron conductivity.
Patent Information
- Application Number
- CN202411832959.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The ternary positive electrode material has irreversible phase change and the dissolution of transition metal ions in lithium-ion batteries, resulting in unstable electrochemical performance and needs to improve its safety and stability.
The modified cathode material is coated with KNbO3 and MoS2 composite materials, and the KNbO3/MoS2 composite materials are prepared by ball milling composite and sintering processes to enhance the diffusion and storage capacity of lithium ions, and further coat the Li7SbO6 material on its surface to improve battery capacity and Cyclic performance.
It improves the battery capacity and cycle life of lithium-ion batteries, enhances charge separation efficiency and electronic conductivity, extends the service life of the battery, and significantly improves the electrochemical performance through double-layer cladding modification.
Smart Images

Figure CN119315036A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to the coating modification of lithium ion battery precursors and positive electrode materials. Background Art
[0002] Ternary cathode materials are widely used in power batteries and small electronic products. Due to their high energy density and low cost, ternary materials have been widely used in electric vehicles, mobile phones, laptops and other devices. Especially in the field of new energy vehicles, ternary lithium batteries have become the mainstream battery type due to their high energy density and good cycle performance. And with the improvement of application requirements, the safety and stability of ternary cathode materials need to be improved urgently.
[0003] In order to improve the electrochemical performance of ternary cathode materials, ternary cathode materials are usually doped or coated. Coating modification can inhibit irreversible phase change and dissolution of transition metal ions, reduce adverse reactions between cathode materials and electrolytes, and reduce the occurrence of side reactions. The selection and application of coating materials are the key research directions of coating modification. Summary of the invention
[0004] In response to the above technical problems, the present application provides a coated modified precursor material and a preparation method thereof, a coated modified positive electrode material and a preparation method thereof, and a lithium-ion battery.
[0005] To achieve the above objectives, this application proposes the following technical solutions: In a first aspect, a coated modified precursor material is provided, including a positive electrode material precursor and a composite material coated on at least a portion of the surface of the positive electrode material precursor, wherein the composite material is a composite material of KNbO3 and MoS2.
[0006] In a second aspect, a method for preparing the aforementioned coated modified precursor material is provided, comprising: KNbO3 and MoS2 were compounded by ball milling to obtain a composite material; The composite material is added to the positive electrode material precursor slurry, stirred for a period of time, and then solid-liquid separation, washing and drying are performed to obtain the composite material coated modified precursor material.
[0007] In a third aspect, a coated modified positive electrode material is provided, comprising a positive electrode material and a composite material coated on at least a portion of the surface of the positive electrode material, wherein the composite material is a composite material of KNbO3 and MoS2.
[0008] In a fourth aspect, a method for preparing a coated modified positive electrode material is provided, comprising: mixing the aforementioned coated modified precursor material with a lithium source and ball milling the mixture, and then sintering the mixture to obtain a positive electrode material coated with a KNbO3 / MoS2 composite material.
[0009] In a fifth aspect, a lithium-ion battery is provided, comprising the aforementioned coated modified positive electrode material.
[0010] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects: The composite material of KNbO3 and MoS2 is coated on the surface of the positive electrode material precursor, and the modified positive electrode material is prepared with the modified precursor material, wherein MoS2 promotes the diffusion of lithium ions and provides more active sites for lithium ion storage, thereby enhancing the lithium storage capacity; KNbO3 has high specific capacitance and high power density characteristics, and after forming a composite material with MoS2, it accelerates the separation and migration of charge carriers, realizes the improvement of charge separation efficiency, and improves the overall electronic conductivity. The KNbO3 / MoS2 composite material has the characteristics of fast ion transfer, high active sites, and a strong synergistic effect. The positive electrode material coated with the composite material has the advantages of increased battery capacity and extended cycle life when applied to lithium-ion batteries.
[0011] By further coating Li7SbO6 material on the surface of the positive electrode material modified by coating the KNbO3 / MoS2 composite material, the specific capacity and cycle performance of the battery can be further improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0013] Figure 1 This is the SEM image of the coated precursor material obtained in Example 1.
[0014] Figure 2 This is the SEM image of the coated positive electrode material obtained in Example 1. DETAILED DESCRIPTION
[0015] The present invention provides a coated modified precursor material, comprising a positive electrode material precursor and a composite material coated on at least a portion of the surface of the positive electrode material precursor, wherein the composite material is a composite material of KNbO3 and MoS2.
[0016] MoS2 promotes the diffusion of lithium ions and provides more active sites for lithium ion storage, thus enhancing the lithium storage capacity; KNbO3 has high specific capacitance and high power density characteristics. After forming a composite material with MoS2, it accelerates the separation and migration of charge carriers, realizes the improvement of charge separation efficiency, and improves the overall electronic conductivity. The KNbO3 / MoS2 composite material has the characteristics of fast ion transfer and high active sites. The positive electrode material coated with the composite material has the advantages of increased battery capacity and extended cycle life when applied to lithium-ion batteries.
[0017] In some preferred embodiments, in the composite material, the molar ratio of KNbO3 to MoS2 is 0.5~1.2:1, for example, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1.0:1, 1.1:1, 1.2:1, etc.
[0018] In some preferred embodiments, the mass ratio of the composite material to the cathode material precursor is 1% to 5%:1, for example, 1%:1, 1.5%:1, 2%:1, 2.5%:1, 3%:1, 3.5%:1, 4%:1, 4.5%:1, 5%:1, etc.
[0019] In some preferred embodiments, the chemical formula of the positive electrode material precursor is Ni x Co y Mn z (OH)2, where 0.7≤x<1, 0≤y≤0.3, 0<z≤0.3, x+y+z =1.
[0020] The present invention provides a method for preparing the aforementioned coated modified precursor material, comprising: KNbO3 and MoS2 were compounded by ball milling to obtain a composite material; The composite material is added to the positive electrode material precursor slurry, stirred for a period of time, and then solid-liquid separation, washing and drying are performed to obtain the composite material coated modified precursor material.
[0021] In some preferred embodiments, the ball milling time is 10-18 hours; the rotation speed of the ball milling is 400-500 r / min.
[0022] The stirring time can be conventionally determined according to the mixing effect requirements. Specifically, in some implementation methods, the stirring time is 5 to 20 hours.
[0023] In some preferred embodiments, the positive electrode material precursor may be a hydroxide precursor; the preferred chemical formula of the hydroxide precursor is Ni x Co y Mn z(OH)2, where 0.7≤x<1, 0≤y≤0.3, 0<z≤0.3, x+y+z =1.
[0024] The hydroxide precursor can be prepared by conventional co-precipitation in the art, or can be obtained commercially.
[0025] The positive electrode material precursor slurry is prepared by adding water to the positive electrode material precursor, and the preparation process can be carried out under the action of mechanical forces such as stirring and ultrasound.
[0026] The present invention also provides a coated modified positive electrode material, comprising a positive electrode material and a composite material coated on at least a portion of the surface of the positive electrode material, wherein the composite material is a composite material of KNbO3 and MoS2.
[0027] In some preferred embodiments, in the composite material, the molar ratio of KNbO3 to MoS2 is 0.5~1.2:1.
[0028] In some preferred embodiments, the aforementioned coated modified precursor material is mixed with a lithium source and then sintered.
[0029] In some preferred embodiments, the coated modified positive electrode material further comprises Li7SbO6, and the Li7SbO6 is coated on the surface of the positive electrode material and the composite material. By further coating the Li7SbO6 material on the surface of the positive electrode material coated and modified by the KNbO3 / MoS2 composite material, more Li can be provided during the charge and discharge process. + , which is used to compensate for the lithium ions consumed by the formation of SEI film in the negative electrode and reduce the loss of lithium ions. The positive electrode material obtained after double-layer coating modification has good interface transmission efficiency, and the cycle and storage performance are significantly improved, thereby comprehensively improving the electrochemical performance of lithium batteries.
[0030] In some preferred embodiments, the amount of Li7SbO6 used is 0.1%~0.8%:1 of the molar amount of the lithium battery positive electrode material, for example 0.1%:1, 0.2%:1, 0.3%:1, 0.4%:1, 0.5%:1, 0.6%:1, 0.7%:1, 0.8%:1, etc.
[0031] The present invention provides a method for preparing a coated modified positive electrode material, comprising: mixing the aforementioned coated modified precursor material with a lithium source, and sintering the mixture to obtain a positive electrode material coated with a KNbO3 / MoS2 composite material.
[0032] The mixing may be carried out by conventional mixing methods in the art, such as solid phase mixing. In order to ensure the uniformity of the mixing, ball milling mixing may be performed.
[0033] In some preferred embodiments, the sintering temperature is 700-1200°C, for example, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, etc.; the sintering time is 12-24h, for example, 12h, 15h, 18h, 20h, 22h, 24h, etc.
[0034] The present invention also provides a method for preparing a coated modified positive electrode material, which includes uniformly mixing a KNbO3 / MoS2 composite coated modified positive electrode material with Sb2O3 and LiOH·H2O, and calcining to obtain a Li7SbO6@KNbO3 / MoS2@NCM positive electrode material.
[0035] In some preferred embodiments, before the KNbO3 / MoS2 composite material coated modified positive electrode material is evenly mixed with Sb2O3 and LiOH·H2O, it also includes the step of mixing Sb2O3 and LiOH·H2O, and then ball milling the mixture to achieve uniform mixing and activation of the two.
[0036] The ratio of Sb2O3 to LiOH·H2O can be conventionally determined according to the stoichiometric ratio of Li7SbO6.
[0037] The uniform mixing can be achieved in a conventional manner, for example, by ball milling, the speed of the ball mill can be controlled at 300-500 r / min, and the duration can be controlled at 2-5 h.
[0038] In some preferred embodiments, the calcination temperature is 500-800°C, for example, 500°C, 600°C, 700°C, 800°C, etc., and the insulation time is 5-8h, for example, 5h, 6h, 7h, 8h, etc.
[0039] The present invention also provides a lithium ion battery, comprising the coated modified positive electrode material as described above.
[0040] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.
[0041] Example 1 Step S1, weigh KNbO3 and MoS2 materials at a molar ratio of KNbO3 to MoS2 of 0.7:1 and mix them evenly, then mill the mixture in a ball mill at a speed of 400 r / min for 16 h to obtain a composite material.
[0042] Sb2O3 and LiOH·H2O were mixed evenly in a molar ratio of 1:14, and the mixture was ball-milled in a ball mill at a speed of 300 r / min for 3 h to obtain a precursor mixture of the desired material Li7SbO6.
[0043] Step S2, preparing a nickel-cobalt sulfate aqueous solution with a total concentration of 2.0 mol / L according to a molar ratio of Ni:Co of 0.90:0.10, preparing a sodium hydroxide aqueous solution with a concentration of 8 mol / L, and preparing an ammonia aqueous solution with a concentration of 10 mol / L; Water at 60°C was used as the bottom liquid of the reactor, and ammonia and NaOH solutions were added to adjust the pH to 12.8, and the ammonia concentration was 0.2 mol / L. During the entire reaction process, nitrogen was introduced into the sealed reactor at a nitrogen flow rate of 2 L / min, and stirring was started at a speed of 500 r / min. A nickel-cobalt sulfate aqueous solution, a sodium hydroxide solution, and an ammonia aqueous solution were introduced into the reactor, and the flow rate of the nickel-cobalt sulfate aqueous solution was controlled to be 120 L / h, the pH of the reaction system was controlled to be 12.8, and the ammonia concentration was controlled to be 0.2 mol / L, the reaction temperature is 60℃, and the nucleation reaction is carried out. With continuous feeding, after 3 hours, the pH of the reaction system is gradually reduced to 11.8, and then the flow rate of the sodium hydroxide aqueous solution is adjusted to continue the particle growth, and the pH of the reaction solution is controlled to be 11.85, and the reaction temperature is controlled to be 55℃. The stirring speed remains unchanged, the feeding is continued, the small crystal nuclei gradually grow, and the sphericity tends to be perfect. Nickel cobalt hydroxide precursor slurry is obtained by coprecipitation. When the particle D50 grows to 4μm, the feeding is stopped to obtain the precursor matrix slurry.
[0044] The mass ratio of the coating material (composite material) to the precursor matrix is controlled to be 3%:1. The composite material prepared in step S1 is made into a slurry, and introduced into the nickel cobalt hydroxide precursor slurry. After reacting for 10 hours, the precursor is washed and dried to obtain a coated modified precursor, and its SEM image is as shown in FIG. Figure 1 shown.
[0045] Step S3, the coated precursor and lithium hydroxide monohydrate are mixed uniformly in a ball mill at a molar ratio of 1:1.1, the rotation speed is 400r / min, the roasting temperature is 900℃, and the insulation time is 15h to obtain KNbO3 and MoS2 composite coated modified LiNi 0.9 Mn 0.1 O2 positive electrode material.
[0046] Step S4, the Li7SbO6 precursor mixture prepared in step S1 is mixed with KNbO3 and MoS2 to form a modified positive electrode material according to the theoretical amount of Li7SbO6 and LiNi 0.9 Mn 0.1 The O2 molar ratio was 0.5%:1 and mixed evenly. The calcination temperature was 700℃ and the insulation time was 6h to obtain Li7SbO6@KNbO3 / MoS2@LiNi 0.9 Mn 0.1 O2 positive electrode material, its SEM image is as follows Figure 2 shown.
[0047] Example 2 Step S1, weigh KNbO3 and MoS2 materials at a molar ratio of KNbO3 to MoS2 of 1.1:1 and mix them evenly, then mill the mixture in a ball mill at a speed of 400 r / min for 16 h to obtain a composite material.
[0048] Sb2O3 and LiOH·H2O were mixed evenly in a molar ratio of 1:14, and the mixture was ball-milled in a ball mill at a speed of 300 r / min for 3 h to obtain a precursor mixture of the desired material Li7SbO6.
[0049] Step S2, preparing a nickel-cobalt sulfate aqueous solution with a total concentration of 2.0 mol / L according to a molar ratio of Ni:Co of 0.90:0.10, preparing a sodium hydroxide aqueous solution with a concentration of 8 mol / L, and preparing an ammonia aqueous solution with a concentration of 10 mol / L; Water at 60°C was used as the bottom liquid of the reactor, and ammonia and NaOH solutions were added to adjust the pH to 12.8, and the ammonia concentration was 0.2 mol / L. During the entire reaction process, nitrogen was introduced into the sealed reactor at a nitrogen flow rate of 2 L / min, and stirring was started at a speed of 500 r / min. A nickel-cobalt sulfate aqueous solution, a sodium hydroxide solution, and an ammonia aqueous solution were introduced into the reactor, and the flow rate of the nickel-cobalt sulfate aqueous solution was controlled to be 120 L / h, the pH of the reaction system was controlled to be 12.8, and the ammonia concentration was controlled to be 0.2 mol / L, the reaction temperature is 60℃, and the nucleation reaction is carried out. With continuous feeding, after 3 hours, the pH of the reaction system is gradually reduced to 11.8, and then the flow rate of the sodium hydroxide aqueous solution is adjusted to continue the particle growth, and the pH of the reaction solution is controlled to be 11.85, and the reaction temperature is controlled to be 55℃. The stirring speed remains unchanged, the feeding is continued, the small crystal nuclei gradually grow, and the sphericity tends to be perfect. Nickel cobalt hydroxide precursor slurry is obtained by coprecipitation. When the particle D50 grows to 4μm, the feeding is stopped to obtain the precursor matrix slurry.
[0050] The mass ratio of the coating material (composite material) to the precursor matrix is controlled to be 3%:1. The composite material obtained in step S1 is made into a slurry, and introduced into the nickel cobalt hydroxide precursor slurry. After reacting for 10 hours, the slurry is washed and dried to obtain a coated modified precursor.
[0051] Step S3, the coated precursor and lithium hydroxide monohydrate are mixed uniformly in a ball mill at a molar ratio of 1:1.1, the rotation speed is 400r / min, the roasting temperature is 900℃, and the insulation time is 15h to obtain KNbO3 and MoS2 composite coated modified LiNi 0.9 Mn 0.1 O2 positive electrode material.
[0052] Step S4, the Li7SbO6 precursor mixture prepared in step S1 is mixed with KNbO3 and MoS2 to form a modified positive electrode material according to the theoretical amount of Li7SbO6 and LiNi 0.9 Mn 0.1 The O2 molar ratio was 0.5%:1 and mixed evenly. The calcination temperature was 700℃ and the insulation time was 6h to obtain Li7SbO6@KNbO3 / MoS2@LiNi 0.9 Mn 0.1 O2 positive electrode material.
[0053] Example 3 Step S1, weigh KNbO3 and MoS2 materials at a molar ratio of KNbO3 to MoS2 of 0.7:1 and mix them evenly, then mill the mixture in a ball mill at a speed of 400 r / min for 16 h to obtain a composite material.
[0054] Sb2O3 and LiOH·H2O were mixed evenly in a molar ratio of 1:14, and the mixture was ball-milled in a ball mill at a speed of 300 r / min for 3 h to obtain a precursor mixture of the desired material Li7SbO6.
[0055] Step S2, preparing a nickel-cobalt sulfate aqueous solution with a total concentration of 2.0 mol / L according to a molar ratio of Ni:Co of 0.90:0.10, preparing a sodium hydroxide aqueous solution with a concentration of 8 mol / L, and preparing an ammonia aqueous solution with a concentration of 10 mol / L; Water at 60°C was used as the bottom liquid of the reactor, and ammonia and NaOH solutions were added to adjust the pH to 12.8, and the ammonia concentration was 0.2 mol / L. During the entire reaction process, nitrogen was introduced into the sealed reactor at a nitrogen flow rate of 2 L / min, and stirring was started at a speed of 500 r / min. A nickel-cobalt sulfate aqueous solution, a sodium hydroxide solution, and an ammonia aqueous solution were introduced into the reactor, and the flow rate of the nickel-cobalt sulfate aqueous solution was controlled to be 120 L / h, the pH of the reaction system was controlled to be 12.8, and the ammonia concentration was controlled to be 0.2 mol / L, the reaction temperature is 60℃, and the nucleation reaction is carried out. With continuous feeding, after 3 hours, the pH of the reaction system is gradually reduced to 11.8, and then the flow rate of the sodium hydroxide aqueous solution is adjusted to continue the particle growth, and the pH of the reaction solution is controlled to be 11.85, and the reaction temperature is controlled to be 55℃. The stirring speed remains unchanged, the feeding is continued, the small crystal nuclei gradually grow, and the sphericity tends to be perfect. Nickel cobalt hydroxide precursor slurry is obtained by coprecipitation. When the particle D50 grows to 4μm, the feeding is stopped to obtain the precursor matrix slurry.
[0056] The mass ratio of the coating material (composite material) to the precursor matrix is controlled to be 5%:1. The composite material prepared in step S1 is made into a slurry, and introduced into the nickel cobalt hydroxide precursor slurry. After reacting for 10 hours, the precursor is washed and dried to obtain a coated modified precursor, and its SEM image is as shown in FIG. Figure 1 shown.
[0057] Step S3, the coated precursor and lithium hydroxide monohydrate are mixed uniformly in a ball mill at a molar ratio of 1:1.1, the rotation speed is 400r / min, the roasting temperature is 900℃, and the insulation time is 15h to obtain KNbO3 and MoS2 composite coated modified LiNi 0.9 Mn 0.1 O2 positive electrode material.
[0058] Step S4, the Li7SbO6 precursor mixture prepared in step S1 is mixed with KNbO3 and MoS2 to form a modified positive electrode material according to the theoretical amount of Li7SbO6 and LiNi 0.9 Mn 0.1 The O2 molar ratio was 0.8%:1 and mixed evenly. The calcination temperature was 700℃ and the insulation time was 6h to obtain Li7SbO6@KNbO3 / MoS2@LiNi 0.9 Mn 0.1 O2 positive electrode material.
[0059] Example 4 The only difference between Example 4 and Example 1 is that step S4 is omitted.
[0060] Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that the precursor is not coated and modified, and the positive electrode is not coated and modified.
[0061] Comparative Example 2 The only difference between this comparative example and Example 1 is that the precursor is only coated with KNbO3.
[0062] Step S1, preparing a nickel-cobalt soluble salt solution with a total concentration of 2.0 mol / L according to a molar ratio of Ni:Co of 0.90:0.10, preparing a sodium hydroxide solution with a concentration of 8 mol / L, and preparing an ammonia solution with a concentration of 10 mol / L; Water at 60°C was used as the bottom liquid of the reactor, and ammonia and NaOH solutions were added to adjust the pH to 12.8, and the ammonia concentration was 0.2 mol / L. During the entire reaction process, nitrogen was introduced into the sealed reactor at a nitrogen flow rate of 2 L / min, and stirring was started at a speed of 500 r / min. A nickel-cobalt sulfate aqueous solution, a sodium hydroxide solution, and an ammonia aqueous solution were introduced into the reactor, and the flow rate of the nickel-cobalt sulfate aqueous solution was controlled to be 120 L / h, the pH of the reaction system was controlled to be 12.8, and the ammonia concentration was controlled to be 0.2 mol / L, the reaction temperature is 60℃, and the nucleation reaction is carried out. With continuous feeding, after 3 hours, the pH of the reaction system is gradually reduced to 11.8, and then the flow rate of the sodium hydroxide aqueous solution is adjusted to continue the particle growth, and the pH of the reaction solution is controlled to be 11.85, and the reaction temperature is controlled to be 55℃. The stirring speed remains unchanged, the feeding is continued, the small crystal nuclei gradually grow, and the sphericity tends to be perfect. Nickel cobalt hydroxide precursor slurry is obtained by coprecipitation. When the particle D50 grows to 4μm, the feeding is stopped to obtain the precursor matrix slurry.
[0063] The composite material obtained in step S1 is made into a slurry, the molar mass ratio of KNbO3 to the total transition metal ions is controlled to be 3%:1, and is introduced into the nickel cobalt manganese hydroxide precursor slurry. After reacting for 10 hours, the slurry is washed and dried to obtain a coated modified precursor.
[0064] Step S2, the coated precursor and lithium hydroxide monohydrate are mixed uniformly in a ball mill at a molar ratio of 1:1.1, the rotation speed is 400r / min, the roasting temperature is 900℃, and the insulation time is 15h to obtain KNbO3 coated modified LiNi 0.9 Mn 0.1 O2 positive electrode material.
[0065] Comparative Example 3 The only difference between this comparative example and Example 1 is that the precursor is only coated with MoS2.
[0066] Step S1, preparing a nickel-cobalt soluble salt solution with a total concentration of 2.0 mol / L according to a molar ratio of Ni:Co of 0.90:0.10, preparing a sodium hydroxide solution with a concentration of 8 mol / L, and preparing an ammonia solution with a concentration of 10 mol / L; Water at 60°C was used as the bottom liquid of the reactor, and ammonia and NaOH solutions were added to adjust the pH to 12.8, and the ammonia concentration was 0.2 mol / L. During the entire reaction process, nitrogen was introduced into the sealed reactor at a nitrogen flow rate of 2 L / min, and stirring was started at a speed of 500 r / min. A nickel-cobalt sulfate aqueous solution, a sodium hydroxide solution, and an ammonia aqueous solution were introduced into the reactor, and the flow rate of the nickel-cobalt sulfate aqueous solution was controlled to be 120 L / h, the pH of the reaction system was controlled to be 12.8, and the ammonia concentration was controlled to be 0.2 mol / L, the reaction temperature is 60℃, and the nucleation reaction is carried out. With continuous feeding, after 3 hours, the pH of the reaction system is gradually reduced to 11.8, and then the flow rate of the sodium hydroxide aqueous solution is adjusted to continue the particle growth, and the pH of the reaction solution is controlled to be 11.85, and the reaction temperature is controlled to be 55℃. The stirring speed remains unchanged, the feeding is continued, the small crystal nuclei gradually grow, and the sphericity tends to be perfect. Nickel cobalt hydroxide precursor slurry is obtained by coprecipitation. When the particle D50 grows to 4μm, the feeding is stopped to obtain the precursor matrix slurry.
[0067] The composite material obtained in step S1 is made into a slurry, the molar mass ratio of MoS2 to the total transition metal ions is controlled to be 3%:1, and is introduced into the nickel cobalt manganese hydroxide precursor slurry. After reacting for 10 hours, the slurry is washed and dried to obtain a coated modified precursor.
[0068] Step S2, the coated precursor and lithium hydroxide monohydrate are mixed uniformly in a ball mill at a molar ratio of 1:1.1, the rotation speed is 400r / min, the roasting temperature is 900℃, and the heat preservation time is 15h to obtain MoS2 coated modified LiNi 0.9 Mn 0.1 O2 positive electrode material.
[0069] The positive electrode materials of Examples 1 to 4 and Comparative Examples 1 to 3 were respectively assembled into batteries in the following manner: the positive electrode material, the binder PVDF, and the conductive agent were mixed in a ratio of 8:1:1, dry-ground for 10 minutes, and then the solvent NMP was added. The positive electrode slurry was obtained by stirring evenly with a homogenizer, and the positive electrode slurry was evenly coated on an aluminum foil; a metal lithium sheet was used as a negative electrode; a lithium ion secondary electrolyte LB-037 (1M LiPF6in DEC:EC:EMC=1:1:1 Vol%) was used as an electrolyte, and Celgard2325 was used as a separator to assemble into a LIR2032 button battery.
[0070] The electrical properties of the battery were tested in the following manner: in a 25°C constant temperature box, the battery was charged at a constant current of 0.1C to a voltage of 4.3V, then charged at a constant voltage of 0.01C and discharged at 0.1C to 3V, and the cycle was repeated twice. The battery was then charged at a constant current of 0.5C to a voltage of 4.3V, then charged at a constant voltage of 0.05C and discharged at 0.5C to 3V, and the charge and discharge capacity was recorded.
[0071] The test results are shown in Table 1. As can be seen from the table, the modification effect of KNbO3 / MoS2 composite coating is better than that of single KNbO3 coating or single MoS2 coating, and the discharge specific capacity and cycle performance are improved. After analysis, this is because MoS2 promotes the diffusion of lithium ions and provides more active sites for lithium ion storage, thereby enhancing the lithium storage capacity; KNbO3 has the characteristics of high specific capacitance and high power density. After forming a composite material with MoS2, it accelerates the separation and migration of charge carriers, realizes the improvement of charge separation efficiency, and improves the overall electronic conductivity. The KNbO3 / MoS2 composite material has the characteristics of fast ion transfer and high active sites. Therefore, the positive electrode material coated with the composite material has the advantages of improved battery capacity and extended cycle life when applied to lithium-ion batteries.
[0072] It can also be seen from Table 1 that by further coating the surface of the positive electrode material with Li7SbO6, the battery not only has better cycle stability, but also has a significant increase in the first cycle capacity at 0.5C. When tested at 0.5C and 3-4.3V, the first cycle discharge capacity is 188.49mAh / g, and the 50-cycle cycle retention rate can reach 97.6%. After analysis, this is because the Li7SbO6 material can provide more Li during the charge and discharge process. + , which is used to compensate for part of the lithium ions consumed by the formation of SEI film at the negative electrode and reduce the loss of lithium ions. The positive electrode material obtained after double-layer coating modification has good interface transmission efficiency, and the cycle and storage performance are significantly improved, thereby comprehensively improving the electrochemical performance of lithium batteries.
[0073] Table 1 The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A coated modified precursor material, characterized in that: It comprises a positive electrode material precursor and a composite material coated on at least a part of the surface of the positive electrode material precursor, wherein the composite material is a composite material of KNbO3 and MoS2.
2. The coated modified precursor material according to claim 1, characterized in that: In the composite material, the molar ratio of KNbO3 to MoS2 is 0.5~1.2:
1.
3. The coated modified precursor material according to claim 1, characterized in that: The mass ratio of the composite material to the cathode material precursor is 1% to 5%:1; The chemical formula of the positive electrode material precursor is Ni x Co y Mn z (OH)2, where 0.7≤x<1, 0≤y≤0.3, 0<z≤0.3, x+y+z =1.
4. The method for preparing a coated modified precursor material according to any one of claims 1 to 3, characterized in that: include: KNbO3 and MoS2 were compounded by ball milling to obtain a composite material; The composite material is added to the positive electrode material precursor slurry, stirred for a period of time, and then solid-liquid separation, washing and drying are performed to obtain the composite material coated modified precursor material.
5. The coated modified positive electrode material is characterized in that: It comprises a positive electrode material and a composite material coated on at least a part of the surface of the positive electrode material, wherein the composite material is a composite material of KNbO3 and MoS2.
6. The coated modified positive electrode material according to claim 5, characterized in that: It also includes Li7SbO6, and the Li7SbO6 is coated on the surface of the positive electrode material and the composite material; The amount of Li7SbO6 used is 0.1% to 0.8% of the molar amount of the positive electrode material; The chemical formula of the positive electrode material is LiNi x Co y Mn z O2, where 0.7≤x<1, 0≤y≤0.3, 0<z≤0.3, x+y+z=1.
7. The method for preparing a coated modified positive electrode material according to claim 5 or 6, characterized in that: include: The coated modified precursor material according to any one of claims 1 to 3 is mixed with a lithium source and ball-milled, and then sintered to obtain a positive electrode material coated and modified by a KNbO3 / MoS2 composite material.
8. The method for preparing a coated modified positive electrode material according to claim 7, characterized in that: The method also includes uniformly mixing the positive electrode material coated with the KNbO3 / MoS2 composite material with Sb2O3 and LiOH·H2O, and calcining the mixture to obtain the obtained product.
9. The method for preparing a coated modified positive electrode material according to claim 8, characterized in that: The sintering temperature is 700-1200°C; the sintering time is 12-24h; The calcination temperature is 500-800° C., and the calcination time is 5-8 hours.
10. A lithium ion battery, characterized in that Comprising the coated modified positive electrode material as described in claim 5 or 6.
Citation Information
Patent Citations
Ternary positive electrode material with double-layer coating structure on surface, and preparation method thereof
CN112289998A
Preparation method of positive electrode material of lithium ion battery and product thereof
CN112614967A
High-performance ternary positive electrode material and preparation method thereof
CN114744184A
Coated modified spinel lithium manganate material as well as preparation method and application thereof
CN115548297A
Antimony-modified high-nickel ternary layered composite positive electrode material as well as preparation method and application thereof
CN116093309A